Factors That Influence the Intention and Behavior in Cybersecurity of The Workers of a Mining Company: An Approach Through the Theory of Planned Behavior - Carlos GALLEGUILLOS; Rafael FIGUEROA; Alexander BÖRGER; Bárbara LETELIER; Camila JUAREZ (Communications of International Proceedings, 2024)
The objective of this research is to evaluate the intention and behavior in cybersecurity of workers of a mining company, for which the theory of planned behavior (TPB) was used, which evaluated variables such as attitude, subjective norm, and behavioral control. perceived, with the intention to have cybersecurity behavior, in addition to evaluating the relationship between intention and behavior in cybersecurity. The research was carried out in only one mining company, in the Atacama region, Chile. The sample was 201 workers from the selected mining company who responded to a survey through the “Forms” platform. It was determined that attitude and perceived behavioral control are positively associated with the intention to have cybersafe behavior. For its part, intention is positively associated with workers' behavior towards digital security.
Keywords: Cybersecurity; theory of planned behavior; mining.